(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Heterotopic pregnancy(HP) is defined as the simultaneous presence of intrauterine and ectopic pregnancies. It is an uncommon but interesting condition with a high mortality rate despite its low incidence. It can be difficult to diagnose due to its diverse clinical manifestations. Due to increase use of artificial reproductive techniques its incidence is raised but rarely occurring in natural conception cycles. The aim of the study is to present the situation of coexistence of intrauterine pregnancy and tubal pregnancy which were occurred in natural conception. In this case study we discussed two cases1st case is 2nd gravida 8 weeks pregnancy with heterotopic pregnancy (one is anembryonic pregnancy with left sided ruptured ectopic pregnancy) 2nd one is 3rd gravida with 7 weeks pregnancy with heterotopic pregnancy with previous history of 2 LUCS (one is incomplete abortion and another one is live tubal pregnancy ) In both cases there was diagnostic dilemma. Both cases firstly presented as vaginal spotting with pain ultimately transvaginal ultrasound showed heterotopic pregnancy. Bangladesh J Obstet Gynaecol, 2023; Vol. 38(1): 46-48